Best Beginnings: Investing in the early years. (2nd September 2020) - Hancock, David
Abstract : This summer, the Children's Commissioner for England produced a comprehensive early years report with a proposal for a new guarantee to give all children in England the best start in life. David Hancock provides a summary of the recommendations